Evaluación de quitosano en el crecimiento y desarrollo de tomate (Solanum lycopersicum, L.) en condiciones de casa de cultivo. - Lanchimba Sopalo, Wilmer Iván (2019)
The investigation was carried out under conditions of cultivation house, in the Experimental Center “La Playita”, belonging to the Technical University of Cotopaxi – La Maná, Ecuador, from april to august of the 2019, with the objective of evaluating the application of the chitosan on the cultivation of the tomato. The seeding was carried out in nursery and the postures later on were transplanted in bags with a franc-sandy floor. The utilized tomato variety was "Amalia". Four treatments were used, consistent in three dilutions of QuitoMax® and a treatment control replied 4 times, the design experimental employee was blocks totally at random. The treatments were T1: Control, T2: 200 mg ha-1, T3: 250 mg ha-1 and T4: 300 mg ha-1. A parcel constituted a replica of 20 plants (20 bags). For the evaluation of the variables of growth and development 40 plants were selected by treatment and 40 fruits for the indicators of quality were carried out an application to foliate to the 12 days after the transplant. The data were processed by means of analysis of variance of double classification and a test of comparison multiple stockings by Tukey (P <0,05) with the statistical package Statistica v. 10.0 for Windows. The obtained results demonstrated that the best applied dose corresponds that of 300 mg ha-1 in 100% of the valued variables, with a yield of 61,9 t ha-1 and an entrance of 7 428,00 USD of value of the production.